Organizational design: meaning, essential characteristic - Efimochkina N. B. (Interactive science, 2017)
the article analyses the implementation of scientific and organizational methods of organizational design of management system . The author elaborately examines the stepwise algorithm of organizational design and shows the real mechanisms of implementation of innovative pilot projects and assessment of their efficiency.
Keywords: инновации; система управления; показатели эффективности; innovations; management system; бенчмаркинг; benchmarking; введение алгоритма пилотного проекта; блок-схемы; диаграммы Ганта; гистограммы загрузки ресурсов; flowcharts; Gant charts; resource loading histograms; performance indicators; декомпозиция работ; структура строителей; introduction of pilot project algorithm; work breakdown; builders structure